Implementasi Algoritme Profile Matching Untuk Perekrutan Karyawan - Mujito Mujito; Basuki Hari Prasetyo; Nasrul Sani (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2019)
IT infrastructure at PT. Citra Multi Service is a very important part in the company where this is all part of the Foundation or framework that supports a system or organization to maintenance. The prospective employee selection process done by checking and selection is manually done by checking one by one the documentary was sent by the applicant, so make appraisers hassles and inefficient and require quite a long time, and the occurrence of human error as well as an assessment of subjective, sometimes the end result is not the best prospective employees. In this study using two aspects and in the aspect there are a few criteria. The basic Technique consists of aspect criteria Desktop Support, Network Engineer, Server Engineer, Security Engineer and Data Center Engineer. On the aspect of Personality consists of Dexterity, communication, discipline, Team Work and Responsibility. Method or Algorithm used is a Matching Profile. The results of this research is an application that produces the decision supporting systems output a rank of each prospective employees, so the management decision makers can see the ability of each candidate employees based on the rank.